2018
DOI: 10.2169/internalmedicine.9737-17
|View full text |Cite
|
Sign up to set email alerts
|

Can Trainees Safely Perform Endoscopic Treatments for Common Bile Duct Stones? A Single-center Retrospective Study

Abstract: Objective There are no reports on whether or not trainees can safely carry out endoscopic procedures for the removal of common bile duct (CBD) stones. The aim of this study was to investigate the efficacy and safety of endoscopic treatments for CBD stones by trainees. Methods Endoscopic retrograde cholangiopancreatography (ERCP) was performed in 1,016 consecutive patients at our institution during the 6-year study period. The endoscopically treated patients with CBD stones were included in this study. Physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…There is conflicting prior data with regards to the success and safety profile of ERCPs with involvement of trainees. 5,32,33 A recent study utilizing the NIS database from 2008 to 2012 found a higher mortality associated with ERCPs in teaching hospitals but no significant difference in the rate of PEP. 34 On the contrary, a recent prospective study did not show any differences in procedural adverse events with the involvement of trainees.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting prior data with regards to the success and safety profile of ERCPs with involvement of trainees. 5,32,33 A recent study utilizing the NIS database from 2008 to 2012 found a higher mortality associated with ERCPs in teaching hospitals but no significant difference in the rate of PEP. 34 On the contrary, a recent prospective study did not show any differences in procedural adverse events with the involvement of trainees.…”
Section: Discussionmentioning
confidence: 99%
“…While Frost et al [14] showed that trainee involvement does not negatively influence either successful cannulation or time to cannulation, other data suggest that trainee involvement might actually increase the use of precut in order to facilitate access to the CBD [11]. With respect to patient safety, although available data [11,14,15] suggest that patient safety is not compromised by trainee involvement, these studies are usually underpowered for the analysis of complication rates.…”
Section: Potential Risk Factorsmentioning
confidence: 99%
“…Only three out 20 studies (15%) report the percentage of procedures completed by trainees without hands‐on intervention from a supervisor 18 , 20 , 21 . Iida et al 20 . report a success rate of 63.3% for common bile duct (CBD) stone clearance, while Voiosu et al 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Explicit estimates of trainee and supervisor caseloads prior to study inception were lacking or unclear in 8/20 (40%) and 16/20 (80%) of studies respectively. Furthermore, the threshold between trainee and trainer is further muddled by the fact that in two studies the definition of expert/supervisor is based on previous experience of only 300 and 500 ERCPs respectively, 20,23 a low volume which practically overlaps caseloads accrued by some trainees during the study period in some of the other included articles. 18,25 Achieving competence in ERCP Table 1.…”
Section: Training Protocol Ercp Trainees and Supervisorsmentioning
confidence: 99%
See 1 more Smart Citation